NEUROLINGUISTIC INDICATORS OF CONSECUTIVE INTERPRETING - DRABIK, Iwona (Comparative Legilinguistics, 2011)
In spite of a large body of research, it has proved difficult to integrate the existing data concerning interpreters’ professional knowledge, their linguistic competence and their psycholinguistic predispositions into a cohesive theoretical framework. The article highlights a coherent and interrelated set of psychological abilities as well as processes constituting a relevant component of translation competence. According to this framework, consecutive interpreting comprises three conceptually related mental processes involving a variety of psycholinguistic factors. These processes are: (1) reception of an initial message, (2) storing of a message, and (3) production of a target message. The message may be received in three ways: (1) on the basis of a text produced by the speaker, (2) via the senses, and (3) through nonverbal communication. Human perception is determined by their cultural background which comprises rules, principles, norms, beliefs – all the cognitive factors which influence their outlook, and according to which they distinguish particular elements of the world and evaluate modes of behaviour, attitudes, etc. Due to the fact that in the analysis of a message, the interpreter has to identify the main ideas and give them their proper relevance in their interpretation, the received information is converted in the human brain into basic conceptual units forming a semantic net.